Relation of Procollagen Type III Amino Terminal Propeptide Level to Sepsis Severity in Pediatrics - Nagwan Y. Saleh; Hesham M. Aboelghar; Sherif S. Salem; Shimaa E. Soliman; Doaa M. Elian (MDPI AG, 2021)
Background: Sepsis is still the main etiology of mortality in pediatric intensive care units (PICUs). Therefore, we performed this study to evaluate the value of procollagen Type III amino-terminal propeptide (PIIINP) as a biomarker for sepsis severity diagnosis and mortality. Method: A prospective study was carried out on 170 critically ill children admitted into the PICU and 100 controls. The performed clinical examinations included calculation of the pediatric risk of mortality. Serum PIIINP was withdrawn from patients at admission and from the controls. Results: PIIINP level was significantly more increased in sepsis, severe sepsis, and septic shock than among the controls (p < 0.001). PIIINP was significantly higher in severe sepsis and septic shock (568.3 (32.5-1304.7) and 926.2 (460.6-1370), respectively) versus sepsis (149.5 (29.6-272.9)) (p < 0.001). PIIINP was significantly increased in non-survivors (935.4 (104.6-1370)) compared to survivors (586.5 (29.6-1169)) (p < 0.016). ROC curve analysis exhibited an area under the curve (AUC) of 0.833 for PIIINP, which is predictive for sepsis, while the cut-off point of 103.3 ng/mL had a sensitivity of 88% and specificity of 82%. The prognosis of the AUC curve for PIIINP to predict mortality was 0.651; the cut-off of 490.4 ng/mL had a sensitivity of 87.5% and specificity of 51.6%. Conclusions: PIIINP levels are increased in sepsis, with significantly higher levels in severe sepsis, septic shock, and non-survivors, thus representing a promising biomarker for pediatric sepsis severity and mortality.